Germline mutations of the LKB1 (STK11) gene in Peutz-Jeghers patients. Issue 5 (1st May 1999) - Wang, Z-J; Churchman, M; Avizienyte, E; McKeown, C; Davies, S; Evans, D G R; Ferguson, A; Ellis, I; Xu, Wen-Huai; Yan, Zhong-Yu; Aaltonen, L A; Tomlinson, I P M
Abstract : Germline mutations of the LKB1 (STK11) serine/threonine kinase gene (chromosome 19p13.3) cause Peutz-Jeghers syndrome, which is characterised by hamartomas of the gastrointestinal tract and typical pigmentation. Peutz-Jeghers syndrome carries an overall risk of cancer that may be up to 20 times that of the general population. Here, we report the results of a screen for germline LKB1 mutations by DNA sequencing in 12 Peutz-Jeghers patients (three sporadic and nine familial cases). Mutations were found in seven (58%) cases, in exons 1, 2, 4, 6, and 9. Five of these mutations, two of which are identical, are predicted to lead to a truncated protein (three frameshifts, two nonsense changes). A further mutation is an in frame deletion of 6 bp, resulting in a deletion of lysine and asparagine; the second of these amino acids is conserved between species. The seventh mutation is a missense change in exon 2, converting lysine to arginine, affecting non-conserved amino acids and of uncertain functional significance. Despite the fact that Peutz-Jeghers syndrome is usually an early onset disease with characteristic clinical features, predictive and diagnostic testing for LKB1 mutations will be useful for selected patients in both familial and non-familial contexts.